Pendidikan & Manajemen Sanggar Tari Tradisional - Taryana, Tatang; Budiman, Agus; Karyati, Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The implementation of dance studios in the community has a function as a forum for non-formal education whose existence is currently growing and developing in the community. Today, there are many dance studios in the community whose orientation is not only in the scope of social activities but has become part of business activities for their implementation. This article aims to provide an overview of the management of traditional dance studios in the Bandung-West Java area, Indonesia, whose management concept has a business orientation. This research was conducted through a qualitative research paradigm using descriptive analysis method. Research data obtained from interviews and documentation. Interviews were conducted with studio managers and dance trainers who teach at the Jaipongan and Classical Dance Studios in Bandung City, West Java, Indonesia. The results of the study indicate that in an effort to realize quality dance studio learning, a dance studio management system is needed that has good management functions based on aspects of planning, organizing, mobilizing, and supervising, so that the implementation of dance education in the studio is able to produce human resources who have reliable expertise in the field of dance. dance and can be used in their daily activities. In addition, good management of art studios has been able to become an economic support for the actors who manage the studios in it. The conclusion of the research results can be a source of reference for prospective new studio developers whose concept will be directed at business management.